Quality Enhancement in Engineering Institutions through Knowledge Management and Total Quality Management - Surya Rao, U.; Pal Pandi, A. (Journal of Engineering Education Transformations, 2007)
In today's competitive environment there is a need to excel in order to survive. To excel, an engineering institution needs to focus on all parts of the institution, optimizing all of its resources. Human resource are the greatest assets of an engineering institution, because, through human resources all other resources are converted Â·into utilities. The management of knowledge in businesses is an important and necessary factor for organizational survival, and to maintain the competitive advantage, organizations need a Total Quality Management (TQM) approach that views knowledge as a potential source of competitive advantage. Knowledge Management (KM) can be viewed as the process of identifying, organizing and managing knowledge resources. We have come to realize that there are only two things (KM& TQM) that need to be practiced in order to achieve excellence in engineering education.